O trabalho do psicopedagogo no contexto escolar - Corsino, Daniela Rodrigues (Universidade Federal do Tocantins, 2025)
This study addresses the work of the psychopedagogue in the school context, emphasizing their role in identifying and intervening in learning difficulties, as well as in promoting an inclusive environment. The research aims to investigate the work of the psychopedagogue in the school context. The specific objectives are: to discuss the role of the psychopedagogue in schools from a historical perspective; to present the legal basis of the psychopedagogue profession in Brazil; to analyze published works on the role of the psychopedagogue in schools; and to reflect on what their effective contribution to the pedagogical process has been. The methodology used is bibliographical and documentary, with analysis of studies published between 2013 and 2023. The results show that the psychopedagogue plays a crucial role in mediating between students, teachers, and families, contributing to the academic and socioemotional development of students in the school environment. In addition, the study highlights the relevance of family participation and the need for public policies that expand access to psychopedagogical services. It is concluded that the role of the psychopedagogue is essential for the construction of a quality education, based on inclusion and respect for the individualities of students.